Judith Leyster’s A Boy and a Girl with a Cat and an Eel: An Intersectional Approach - Elizabeth Sutton (Arts)
In A Boy and a Girl with a Cat and an Eel, concerns about class, decorum, and civility intersected with contemporary dialogue about the distinction between humans and animals, specifically, how human children needed to be educated to be distinguished from the wild, uncivilized state of animals and peasants. Both animals held significance surrounding behaviors that separated the moral from the immoral; cats and eels were pets and food, and they were used in baiting pastimes: cat clubbing and eel pulling. Paired with the children, Leyster’s choice of animals raised multiple moral questions and allowed for multiple interpretations, making the work widely appealing and setting Leyster apart in a tight market for genre paintings. These layers of possible meanings continue to make the work compelling today and shed light on how visual culture reflected and reinforced human–animal and social class distinctions.